Influence of cell size on soil loss estimation in Universal Soil Loss Equation (USLE) model - Hazizi Esa, 1975-; Muhamad Nor Said; Zulkifli Yusop, supervisor; Fakulti Geoinformasi dan Harta Tanah (2014)
Thesis (Sarjana Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2014